THE EFFECT OF COMPANY SIZE, CAPITAL STRUCTURE, MANAGERIAL OWNERSHIP, INSTITUTIONAL OWNERSHIP AND DISCLOSURE OF CORPORATE SOCIAL RESPONSIBILITY ON COMPANY VALUE WITH PROFITABILITY AS A MODERATING VARIABLE IN PROPERTY AND REAL ESTATE COMPANIES LISTED IN IDX - Lubis, Nurliza (Asosiasi Dosen Akuntansi Indonesia, 2019)
The objectives of this study are to determine and analyze the effect of Company Size, Capital Structure (DER), Managerial Ownership, Institutional Ownership, and Corporate Social Responsibility both simultaneously and partially on Corporate Value (PBV), and analyze Profitability (ROA) to moderate the relationship between Size Companies, Capital Structure (DER), Managerial Ownership, Institutional Ownership, and Corporate Social Responsibility with respect to Company Values ​​(PBV) of property and real estate listed on the Indonesia Stock Exchange in 2013-2017. The research population is property and real estate companies listed on the Indonesia Stock Exchange in 2013-2017 with 49 companies. The sample was selected using a purposive sampling method that produced 30 sample companies. Testing the first hypothesis uses multiple linear analysis, test the coefficient of determination, F test and t test, while the second hypothesis for moderating variables using the residual test. The results of this study indicate that Company Size has a positive and insignificant effect on Corporate Values, Capital Structure has a positive and significant effect on Firm Value, Managerial Ownership has a positive and not significant effect on Firm Value, Institutional Ownership has a positive and significant effect on Firm Value, Corporate Social Responsibility has a negative and insignificant effect on Corporate Values, and Profitability is not a variable that is able to moderate Company Size, Capital Structure, Managerial Ownership, Institutional Ownership, and Corporate Social Responsibility towards property and real estate company values ​​listed on the Indonesia Stock Exchange in 2013-2017.